RED BETEL LEAF EXTRACT SERUM (Piper ornatum) AS AN ALTERNATIVE ANTI-HEAD LICE TREATMENT - Rizal Umar Z; Riyadatus Solihah; M Shofwan Haris (NHM PRESS, 2022)
Lice (Pediculus humanus capitis) or known as head lice are ectoparasites that live on the human scalp, the main symptom felt is itching on the scalp caused by lice bites on the scalp. Lice are often found in children aged 7-10 years and also in adults, lice can live on the scalp, body and hair of the pubic area, and can cause itching, scabs, loss of concentration, lack of sleep, and lack of confidence. One way to overcome this is to use anti-lice shampoo. Some studies state that betel leaf extract can kill head lice. Thus, article aims to find out what serum concentration of red betel leaf extract (Piper ornatum) is effective against the death of head lice (Pediculus humanus capitis).